Strategi Pengembangan UMKM dalam Meningkatkan Ekonomi Masyarakat Melalui Pokdarwis di Desa Kemiri, Kecamatan Panti, Kabupaten Jember - Yunita Dwi Wulansari; Julia Shandra Afcarina; Shalsa Aina Widi Zahrafani; Wafiatul Afifah (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Eduwisata village is a form of development of a village that combines elements of tourism with education and learning. The establishment of eduwisata village aims to make people aware of the importance of culture and the environment. In addition, eduwisata village is used as a means of empowering the community's economy. In eduwisata village,there are communities that play a role in increasing the value of the production sector, UMKM, and the economy as well as the economic potential of the village itself. In the process of developing the eduwisata Village program, there is cooperation with various agencies such as local governments, educational institutions, local communities, and the private sector. This study uses the theory of Smelser and Swedberg (2005) suggests that economic sociology focuses more on sociological analysis of economic processes, such as the formation of prices (agreements) between actors with economic actors, the interaction between the economy and other institutions in society, and institutional dynamics and cultural parameters that become the foundation.